Dynamic changes and driving factors of rural settlements at the county level in a rapidly urbanizing province of China from 2000 to 2020 - Xu, Yan; Zhang, Runsen; Wu, Wenchao; Xu, Chen; Yu, Cheng; Chen, Dechao; Liu, Yumei (Frontiers in Environmental Science, 2023)
Urbanization and industrialization in developing countries has contributed to great changes in rural settlements, which presents an increasing threat to rural sustainability. Spatiotemporal changes in rural settlements at the county level are significant to land use planning and are not clear in the highly urbanized regions. This study considered Jiangsu, one of the most urbanized provinces of China, as an example and investigated the spatial variation in rural settlements and their socioeconomic driving factors during the period of 2000 to 2020 using mixed geographic weighted regression. The results showed that the area of rural settlements in the highly urbanized province expanded from 2000 to 2015 following a decrease in the rural population, but then began to decrease from 2015. There were obvious spatial differences in the rural settlements in the counties of Jiangsu Province. The area of rural settlements in the different counties maintained a positive association with the rural population and cropland but had a negative correlation with the rural production value in 2000. By 2020, the area of rural settlements was only positively associated with the rural population. The correlation between the area of rural settlements and rural population continually decreased from 2000 to 2020. The area of rural settlements had no significant association with the area of urban settlements. The expansion of rural settlements mainly occurred at the expense of cropland. The decrease in the rural settlements was accompanied by an increase in the urban settlements and an expansion of cropland. The policy implications arising from this study are presented to provide guidance for rural development at the county level and ensure rural sustainability.